Ecological Risk of Soil Heavy Metal and Organic Pollutants Combined Pollution - Duan, Wenqi (International Journal of Natural Resources and Environmental Studies, 2025)
This paper focuses on soil pollution. It points out that soil is the fundamental resource for human survival and the construction of civilization, and its pollution problem is severe. It elaborates on the types of single soil pollution and combined soil pollution, emphasizes that combined pollution is the main form and causes huge harm. For example, the combined pollution of heavy metals and organic pollutants is common in various pollution sources, which can change soil microorganisms, affect plant growth and endanger human health. It also mentions the ecological risks of combined pollution at the food chain level and the related research technical means. Finally, it shows that soil combined pollution has become the main form, the ecological risk assessment based on the food chain or food web is more realistic, and the development of molecular technologies provides new methods for evaluating its ecological risks.